Donations, risk attitudes and time preferences: A study on altruism in primary school children - Silvia Angerer; Daniela Glätzle-Rützler; Philipp Lergetporer; Matthias Sutter (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2015)
We present experimental evidence from a bilingual city in Northern Italy on whether the language spoken by a partner in a prisoner's dilemma game affects behavior and leads to discrimination. Running a framed field experiment with 828 six- to eleven-year old primary school children in the city of Meran, we find that cooperation generally increases with age, but that the gap between cooperation among in-group members and cooperation towards children speaking another language is considerable and increasing with age. This gap is due to both, in-group favoritism and language group discrimination.
Keywords: C91; C93; D03; 330; cooperation; discrimination; language; children; experiment